Respuesta :

Answer:x1 = 1, x2 = - 1, x3 = 3

Step-by-step explanation:

x1 + 2x2 - x3 = - 4 - - - - - - - - - -1

x1 + 2x2 + x3 = 2 - - - - - - - - - -2

- x1 - x2 + 2x3 = 6 - - - - - - - - - -3

Let us eliminate x1 and x2. Subtracting equation 2 from equation 1, it becomes

-2x3 = - 6

x3 = -6/-2

x3 = 3

Adding equation 2 to equation 3, it becomes

x2 + 3x3 = 8 - - - - - - - - - - - 4

Substituting x3 = 3 into equation 4, it becomes

x2 + 3 × 3 = 8

x2 + 9 = 8

x2 = 8 - 9 = -1

Substituting x2 = -1 and x3 = 3 into equation 2, it becomes

x1 + 2 × -1 + 3 = 2

x1 - 2 + 3 = 2

x1 + 1 = 2

x1 = 2 - 1 = 1

Let us check by substituting x1 = 1, x2 = -1 and x3 = 3 into equation 1. It becomes

1 + 2 × - 1 - 3 = - 4

1 - 2 - 3 = - 4

-1 - 3 = - 4

-4 = - 4